Hydrogen‐Induced Conversion of SnS2 into SnS or Sn: A Route to Create SnS2/SnS Heterostructures. Issue 33 (21st July 2022) - Felton, James; Blundo, Elena; Kudrynskyi, Zakhar; Ling, Sanliang; Bradford, Jonathan; Pettinari, Giorgio; Cooper, Timothy; Wadge, Matthew; Kovalyuk, Zakhar; Polimeni, Antonio; Beton, Peter; Grant, David; et al.
Abstract: The family of van der Waals (vdW) materials is large and diverse with applications ranging from electronics and optoelectronics to catalysis and chemical storage. However, despite intensive research, there remains significant knowledge‐gaps pertaining to their properties and interactions. One such gap is the interaction between these materials and hydrogen, a potentially vital future energy vector and ubiquitous processing gas in the semiconductor industry. This work reports on the interaction of hydrogen with the vdW semiconductor SnS2, where molecular hydrogen (H2 ) and H‐ions induce a controlled chemical conversion into semiconducting‐SnS or to β‐Sn. This hydrogen‐driven reaction is facilitated by the different oxidation states of Sn and is successfully applied to form SnS2 /SnS heterostructures with uniform layers, atomically flat interfaces and well‐aligned crystallographic axes. This approach is scalable and offers a route for engineering materials at the nanoscale for semiconductor technologies based on the earth‐abundant elements Sn and S, a promising result for a wide range of potential applications. Abstract : Hydrogen is used to convert tin disulfide to tin sulfide in a controllable and scalable process. The conversion produces a uniform heterostructure with a step‐like interface and well‐defined vibrational and optical properties.